Analysis of NH3 Content, Individual Characteristics and Respiratory Scavenger Complaint in Landfills Benowo Rubbish and Not Scavenger Around Landfills Benowo Surabaya - Herman Bagus Dwicahyono (JURNAL KESEHATAN LINGKUNGAN, 2017)
Trash are things that cannot be used or have been dumped which formed by human activities and soiled environment then became source of disease. One of high group that greater affected with trash in final disposal is scavenger because they do some direct contact everyday. This study aims to identify NH3 contents, individual characteristic and respiratory complaint for scavenger. Not only that, but also to analyze respiratory complaint according to individual characteristic. This study is observational with quantitative descriptive study and cross sectional design study. The result shows that trash management in final disposal Benowo Surabaya has been implemented a sanitary landfill system based on Undang-Undang RI No. 18 Tahun 2008 Tentang Pengelolaan Sampah. Kadar gas NH3 under quality standard stated by Governor Regulation East Java No.10 Tahun 2009 is 113.9 Î¼g/Nm3 in final disposal and 28.4 Î¼g/Nm3 in non-final disposal. Result shows that almost all respondent was about 35 to 44 years old with Body Mass Index status is overweight, exposured to passive smokers, and had disease history. Almost 65% of total respiratory complaint was happened with scavenger and 89% with non scavenger. The conclusion is trash management in final disposal Benowo Surabaya has been implemented sanitary landfill system, ambient air measurement with indicator in trash final disposal and non-trash final disposal still under quality standard. Almost all respondent who included in scavenger group and nonscavenger group still have a low respiration complaints. There are differences group based on age between respondent who has low and moderate respiration complaints